Eksperimen Pengaruh Kecepatan Pada Diameter Nozzle 2,5 mm dalam Proses Laser Cutting - Masri; Suhaeri; Machmud, M. Nizar; Zainuddin; Saifuddin; Azhar (Yayasan Kawanad, 2023)
This experimental study examines the impact of speed variations on the 2.5 mm nozzle diameter in low-carbon steel laser cutting. The primary objective is to optimize the roundness of the cut by considering cutting speed factors. Through a series of experiments conducted on low-carbon steel plates measuring 200 mm x 200 mm, utilizing a 2.5 mm nozzle diameter with speed variations of 2, 3, and 4 m/minute, the research measures roundness quality using a digital caliper. Results indicate that cutting speed influences roundness quality, with the lowest deviation observed at a speed of 2 m/minute and the highest at 3 m/minute. The study also highlights that increased cutting speed and the use of a larger nozzle require higher gas pressure.